Analisis Pembelian Fitur Premium Pada Pengguna Aplikasi Spotify Menggunakan Variabel Hedonic Motivation System - Randy Indraswara; Komang Candra Brata; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Music is one of entertainment that is relatively easy and is often accessed in the digital world. Many music application developers compete to provide the best applications to satisfy the desires of world music lovers, especially in Indonesia. One application that is popular and popular right now in the music application is Spotify. With an assessment of the standard music player application, Spotify with premium or paid features already meets the requirements to be an excellent application for playing music judged by appearance, song completeness, standard features such as creating playlists, radio and others, sound quality, additional features such as music charts, total song listeners, and events regularly held by Spotify. In this study using the Hedonic Motivation System variable to analyze the motivation of premium users of the Spotify music player application in purchasing premium features because in the hedonic motivation system it has variables that are used to analyze the motivation of users of premium features which are seen in the motivation of customer pleasure and loyalty in the Spotify music application . It is expected that by using the Hedonic Motivation System variable can find out the results of the analysis of the motivation of users of the Spotify application premium features in purchasing premium features. Based on the explanation above, it is expected that with this research the success rate of the Spotify music player application can be seen as a reference for developers to develop online music player applications.